UPAYA PEMERINTAH MELESTARIKAN KEBERADAAN SATWA LANGKA YANG DILINDUNGI DARI KEPUNAHAN DI INDONESIA - A.A. Istri Agung Kemala Dewi; Made Gde Subha Karma Resen (Kertha Negara : Journal Ilmu Hukum, 2014)
This paper has the title “The Government Efforts to Conserve the Existence ofEndangered Species Which Protected From Extinction in Indonesia”. Survival a varietyof endangered species which protected in Indonesia threatened with extinction due toenvironmental destruction by nature and human activity. The research method using thenormative legal research methods research conducted using the approach tolegislation. In the paper the problem issue is about the efforts of the government toprotect endangered species in Indonesia and what sanction government give to thecriminal who do the trafficking of the endangered species trade-us. The conclusionsobtained are the efforts of the government in term of caring for endangered species inIndonesia by publishing legislation and conservation of the endangered species. As wellto give prison sanctions to the criminal maximum 5 (five) year and the maximum fines isRp. 100.000.000,00 (one hundred million) for the criminal who doing endangered speciestrafficking based on the provisions of section 4 paragraph 2 of Law No. 5 of 1990Concerning Conservation of Natural Resources and Ecosystem.